Development of Problem-Solving Instruments Test at Rotational Dynamics and Equilibrium of Rigid Bodies Topic - Sipahutar, Angelson Fery Estomihi; Doloksaribu, Maryati Evivani ((IPER) Indonesian Physics Education Research, 2024)
The ability to think at a higher level (HOTS) refers to the cognitive thinking process of students at a higher level, which evolves from various cognitive concepts and learning taxonomies, such as problem-solving methods. Based on the observations conducted by researchers at SMAN 5 Medan, the current assessment does not prioritize problem-solving skills. This research aims to develop a test instrument that can measure problem-solving skills in students with a high level of validity and reliability. The method used in this development is the research and development model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). In summary, the steps in this development include 1) problem identification and analysis. 2) designing a problem-solving test instrument. 3) developing the problem-solving test instrument to a suitable level. 4) testing the problem-solving test instrument on a small and large scale. 5) analysis the validity of the test instrument and the quality of test items. The result of this research is a developed problem-solving test instrument in the form of essays, meeting the criteria for a high-quality test instrument, and suitable test items.